2020
DOI: 10.3389/fnhum.2020.00171
|View full text |Cite
|
Sign up to set email alerts
|

Central and Peripheral Shoulder Fatigue Pre-screening Using the Sigma–Lognormal Model: A Proof of Concept

Abstract: Background: Clinical tests for detecting central and peripheral shoulder fatigue are limited. The discrimination of these two types of fatigue is necessary to better adapt recovery intervention. The Kinematic Theory of Rapid Human Movements describes the neuromotor impulse response using lognormal functions and has many applications in pathology detection. The ideal motor control is modeled and a change in the neuromuscular system is reflected in parameters extracted according to this theory. Objective: The ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 82 publications
0
10
1
Order By: Relevance
“…Repetitive movements, such as shooting in handball, generate neuromuscular fatigue and, therefore, muscular and kinematic adaptations [ 46 ] that can lead to injuries [ 47 ]. Thus, detecting shoulder fatigue is crucial to avoid injuries [ 48 ]. In our study, we conducted a fatigue protocol consisting of 20 repetitions at 180°/s.…”
Section: Discussionmentioning
confidence: 99%
“…Repetitive movements, such as shooting in handball, generate neuromuscular fatigue and, therefore, muscular and kinematic adaptations [ 46 ] that can lead to injuries [ 47 ]. Thus, detecting shoulder fatigue is crucial to avoid injuries [ 48 ]. In our study, we conducted a fatigue protocol consisting of 20 repetitions at 180°/s.…”
Section: Discussionmentioning
confidence: 99%
“…Several observational studies have suggested that the symptoms of cognitive deficiency can be obvious with the augmentation of RT. 22 , 23 , 24 There is evidence in UKB to support RT as a suitable proxy for cognitive function. 25 In addition, RT was significantly correlated with the digit symbol substitution test in our study population ( P <0.001).…”
Section: Methodsmentioning
confidence: 99%
“…Serum lactate and IL-6 have been identified as the most accurate and valid biomarkers to measure muscle fatigue, although they are influenced by workload conditions and timing of testing with respect to exercise[ 27 ]. Other non-invasive methods have been employed for the detection of peripheral fatigue ( e.g., acoustic myography)[ 28 ]. On the other hand, central fatigue can be assessed either with percutaneous nerve stimulation[ 29 ] or transcranial magnetic stimulation during maximal contractions[ 30 ].…”
Section: Assessment Of Fatiguementioning
confidence: 99%